Christian Martyrs Under Islam: Religious Violence and the Making of the Muslim World by Christian C. Sahner (American Journal of Islam and Society, 2020)
The study of Christian martyrdom in the early Islamic world can be situated within the wider study of the Islamization of the Middle East, and by extension, Muslim-Christian relations. Similar works pertaining to thisBook Reviews 153 field are Richard Bulliet’s Conversion to Islam in the Medieval Period: An Essay in Quantitative History (1979) and Fred Donner’s Narratives of Islamic Origins: The Beginnings of Islamic Historical Writing (1998).To read the full book review, download the PDF file on the right.